Pengaruh Kadar Lempung Dan Kadar Air Pada Sisi basah Terhadap Nilai CBR Pada Tanah Lempung Kepasiran (Sandy Clay) - Muhammad Iqbal; S A Nugroho; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
CBR (California Bearing Ratio) is one method for determining the bearing capacity of the subgrade . In highway planning , subgrade bearing capacity will affect the pavement thickness, the higher bearing capacity of subgrade makes the pavement thickness which needed to withstand the traffic load is getting thinner. Research conducted at the Laboratory of the CBR value is generally only done on the condition of the water content in a state of OMC and saturated, this study investigated the changes of CBR value with moisture content in the range of OMC to saturated of the sandy clay soils, and with clay in different contents. The results of this study indicate that, when the soil is compacted at OMC conditions, increasing contents of clay reduce CBR values, and submersion decreases CBR values of 14,294% at the top of sample and of 13,167 % at the bottom of sample. When soil is compacted with moisture content above OMC, increasing contents of water reduce CBR values. Key Words: CBR, clay, water content